Quality index of raw gilthead sea bream - VARELTZIS (Κ. ΒΑΡΕΛΤΖΗΣ), K.; VASILIADOU (Σ. ΒΑΣΙΛΕΙΑΔΟΥ), S.; SOULTOS (Ν. ΣΟΥΛΤΟΣ), N. (Journal of the Hellenic Veterinary Medical Society, 2018)
Sensorial, biochemical and microbiological methods were used in order to evaluate the quality of the raw gilthed sea bream. Whole fish was stored in ice and in modified gas atmosphere consisting of 70% carbon dioxide and 30% nitrogen. At regular intervals during refrigerated storage Malondialdehyde- MDA^g/kg), Total Volatile Bases-N - TVB-N (mg/100g), odour and flavor scores and various types of micro-organisms were determined. Fatty acid contents were also measured along the cold storage. The results showed that the quality parameters used for the evaluation of raw gilthed sea bream could form a preliminary model for quality index of farmed euryhaline fin fish in our country.